MALIGNANT CATARRHAL FEVER IN AMERICAN BISON (Bison bison) IN SLOVENIA - Starič, Jože; Ježek, Jožica; Cociancich, Vasilij; Gombač, Mitja; Hostnik, Peter; Toplak, Ivan (Slovenian Veterinary Research, 2015)
Summary: Malignant catarrhal fever (MCF) is a ubiquitous disease of cattle and other ruminants caused by ovine herpesvirus-2 (OvHV-2) in Europe and other continents and alcelaphine herpesvirus-1(AlHV-1) in Africa. In March 2010 MCF was recognized in small private zoological garden in three American bison (Bison bison) imported from Vienna. They were housed in an enclosure next to llamas, goats and domestic sheep, with direct contact between all mentioned species. Typical clinical signs of the acute head and eye form of MCF were observed, with especially inflammation of conjunctives, oral and nasal mucosa and marked depression. Mortality was 100%. Necropsy findings in one bison were consistent with MCF. Acute ulcerative abomasitis and omasitis, acute hemorrhagic enterotyflitis, acute purulent bronchitis and moderate emaciation were found. The histopathology revealed mixed lymphohistiocytic and neutrophilic vasculitis in the brain, meninges, liver, spleen, heart, lungs and mixed lymphohistiocytic and neutrophilic hepatitis and adrenalitis. OvHV-2 DNA was detected post-mortem in tissue samples by PCR. Direct sequencing of the PCR product confirmed 100% nucleotide identity to OvHV-2 strain BJI035 and closely related to two OvHV-2 positive sheep samples collected in 2007. These are the first case of MCF confirmed by laboratory diagnostic methods in Slovenia. Furthermore, these are also the first cases of MCF in American bison in Slovenia.